Reconhecimento constitucional: desafios à cidadania brasileira no Estado Democrático de Direito - Zilli, Tiago (2020)
This work was developed within the research line of Social Relations and Dimensions of Power, which focuses on disseminating works that address studies of democracy in the paradigm of the contemporary Constitutional State. In this context, the notion of citizenship is examined from its first attempt at positivization through the formation of the Brazilian State and its symbolic position within peripheral constitutionalism, demonstrating that Brazilian citizenship is reduced to the quality of sub-citizenship. Based on the reading of Axel Honneth's theory of recognition, a discursive window will be opened that aims to demonstrate the precepts of legal recognition and its manifestation through constitutional positivization in the 1988 Constitution, as well as to erect the delimitations that demonstrate recognition as a form of institutional solidarity through the manifestation of constitutional patriotism. At the end, we will direct our perspective to the challenges that permeate the concreteness of the pillars of citizenship exposed by the Federal Constitution.